2007
DOI: 10.1002/cncr.22971
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of small cell carcinoma of the prostate

Abstract: Objective To assess the prevalence and pattern of myocardial fibrosis as detected by delayed enhanced magnetic resonance imaging (DE‐MRI) in patients with systemic sclerosis (SSc), and to evaluate a possible association between myocardial fibrosis and cardiac arrhythmias. Methods Forty‐one patients with SSc underwent 24‐hour Holter monitoring, Doppler echocardiography, and DE‐MRI following gadolinium administration. Results Technically acceptable DE‐MRIs were obtained in 36 patients with SSc. Enhancement on DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 18 publications
2
90
1
Order By: Relevance
“…These tumors generally exhibit aggressive behavior similar to their counterparts in the lung and may present with various paraneoplastic syndromes or endocrinopathies. 12 In a review of 83 patients with small cell carcinoma of the prostate by Spiess et al 13 , 75.6% of patients presented with metastatic disease at diagnosis, and the median survival of all patients was 13.1 months. A literature review by Abbas et al 12 found a median survival of 9.8 months and a 5-year OS of 0.9%.…”
Section: Seer Analysis Of Rare Prostate Cancer Variants Dm Marcus Et Almentioning
confidence: 99%
“…These tumors generally exhibit aggressive behavior similar to their counterparts in the lung and may present with various paraneoplastic syndromes or endocrinopathies. 12 In a review of 83 patients with small cell carcinoma of the prostate by Spiess et al 13 , 75.6% of patients presented with metastatic disease at diagnosis, and the median survival of all patients was 13.1 months. A literature review by Abbas et al 12 found a median survival of 9.8 months and a 5-year OS of 0.9%.…”
Section: Seer Analysis Of Rare Prostate Cancer Variants Dm Marcus Et Almentioning
confidence: 99%
“…In descending order of frequency, men with prostatic SCC most commonly present with voiding, neurologic (confusion, sensory/motor deficits), and/or constitutional symptoms [3]. SCC of the prostate arises in men with pre-existing adenocarcinoma who have received androgen deprivation in nearly half of cases [2,4,5]. This is believed to occur either due to adaptive dedifferentiation of malignant cells under the influence of ADT or the selective pressures of ADT favoring the proliferation of androgen receptor negative neuroendocrine cells [4].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients present with metastatic disease. The most common sites of metastases are the bones, retroperitoneal lymph nodes, liver, lungs, and brain [4]. Therapeutic strategies are largely derived from experience with small cell lung cancer and retrospective reviews as data from randomized controlled trials with prostatic SCC is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Radical prostatectomy alone has been curative in selected patients with small-burdened and early SCPCa. [5] Spiess et al [7] believe that surgical resection with or without radiation therapy combined with chemotherapy should be considered as a treatment strategy in local or early SCPCa. This modality may provide better local control and a potential survival benefit.…”
Section: Discussionmentioning
confidence: 99%